2019
DOI: 10.1021/acs.analchem.9b04467
|View full text |Cite
|
Sign up to set email alerts
|

Native Hydrophobic Interaction Chromatography Hyphenated to Mass Spectrometry for Characterization of Monoclonal Antibody Minor Variants

Abstract: Conventionally, hydrophobic interaction chromatography (HIC) uses mobile phases with high salt concentration that are not compatible with mass spectrometry (MS). Here we describe development of an HIC method coupled with MS detection (HIC-MS) utilizing an aqueous mobile phase with a low concentration of a volatile salt for characterizing recombinant monoclonal antibody (mAb) posttranslational modifications (PTMs). The ability of HIC to separate the oxidation and free thiol variants of the mAbs enables their is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 36 publications
0
40
0
Order By: Relevance
“…The use of volatile mobile phases allows the hyphenation of IEC (31)(32)(33)(34), SEC (35)(36)(37), HIC (38,39), RPLC (40), and affinity chromatography (AC)(41-44) techniques to native MS. LC-nMS separates mAb variants prior to the entrance into the MS system, significantly improving sensitivity, dynamic range, and thus the detection of minor variants by limiting competition effects during the MS ionization process. For instance, the direct hyphenation of IEC to MS utilizing low ionic strength eluents on a strong cation exchange (SCX) stationary phase enabled MS data generation from minor mAb variants, and intact mass analysis of various PTMs, such as lysine truncation, glycosylation, and deamidation (mass shift of +1 Da relative to the main peak) (33).…”
Section: Intact Mass Analysis 11 Native Mass Spectrometry (Nms)mentioning
confidence: 99%
See 1 more Smart Citation
“…The use of volatile mobile phases allows the hyphenation of IEC (31)(32)(33)(34), SEC (35)(36)(37), HIC (38,39), RPLC (40), and affinity chromatography (AC)(41-44) techniques to native MS. LC-nMS separates mAb variants prior to the entrance into the MS system, significantly improving sensitivity, dynamic range, and thus the detection of minor variants by limiting competition effects during the MS ionization process. For instance, the direct hyphenation of IEC to MS utilizing low ionic strength eluents on a strong cation exchange (SCX) stationary phase enabled MS data generation from minor mAb variants, and intact mass analysis of various PTMs, such as lysine truncation, glycosylation, and deamidation (mass shift of +1 Da relative to the main peak) (33).…”
Section: Intact Mass Analysis 11 Native Mass Spectrometry (Nms)mentioning
confidence: 99%
“…The introduction of new hydrophobic resins enabled HIC to be coupled to MS using ammonium acetate in combination with one or more organic modifiers in the mobile phase, for the characterization of both mAbs (46) and ADCs (40). As an example, Wei et al reported the development of a HIC-nMS method for the determination of minor mAb variants including oxidation, glycation, and free thiol variants by utilizing 150 mM ammonium acetate on a polypropyl UHPLC wide-pore HIC column, which both ensure retention and adequate MS sensitivity for the characterization of low-abundance peaks (38). In another recent study, Chen et al described the development of a native RPLC-nMS method using a 50 mM ammonium acetate and water/isopropanol mobile phase for the separation of intact ADCs (40).…”
Section: Intact Mass Analysis 11 Native Mass Spectrometry (Nms)mentioning
confidence: 99%
“…Because HIC can separate DAR species under native conditions, it is used not only analytically for DAR determination but also for purification. 13,15,16) Furthermore, a combination of site-specific conjugation followed by preparative HIC purification can provide site-specific and homogeneous-DAR ADCs. 16) However, HIC separation has some disadvantages.…”
Section: Hplc/uv Approachmentioning
confidence: 99%
“…13,15,16) Furthermore, a combination of site-specific conjugation followed by preparative HIC purification can provide site-specific and homogeneous-DAR ADCs. 16) However, HIC separation has some disadvantages. This technique does not provide compatibility with MS analysis because HIC-HPLC requires a high initial concentration of low volatility salts in the mobile phase.…”
Section: Hplc/uv Approachmentioning
confidence: 99%
“…Matrix-assisted laser desorption ionization time-of-flight (MALDI-TOF/TOF) MS with higher collision energies is also a valuable choice for MS1/MS2 analysis of glycans (Chen, 2015 ; Chen et al, 2016 ). Electrospray ionization (ESI)-TOF MS has also been reported to be efficient for glycosylation analysis of intact IgG molecules (Wei et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%